A preliminary study understanding the possibility and benefits of solar photovoltaic collector integration with vertical green balconies in building facade reconstruction - Wu, Zhang; Chul-Soo, Kim (Frontiers in Energy Research, 2023)
Abstract:Thefacadesofbuildingsprovidesignificantpotentialforphotovoltaicpanelsintegration,allowingrenewableenergydeploymentwithinthebuiltenvironment.Inliterature,variousoptions,suchasbuilding-integratedphotovoltaics,building-integratedphotovoltaics-thermalcollectors,building-attachedphotovoltaics,androoftopphotovoltaics,havealreadybeenexplored.However,thisstudyaimedtodevelopanewsolarphotovoltaiccollectors’integrationwithvertical-greenbalconiesinoldhigh-risebuildingsconsideringthefaçadereconstructionconceptsmainlyfocusingonthewaterheatingapplication.Theobjectiveofthisstudyistoconductapreliminaryresearchstudyinvestigatingsuchintegrationpossibilitieswitholdbuildingsconsideringthefaçadereconstructionconcepts,followedbyexploringvariousbenefits.Forthis,anoldhigh-risebuildingwasrebuiltscientificallyandrationally.PHOENICStoolwasusedtogaugeandassessthebuilding'swindenvironmentfirst,followedbythesolarphotovoltaiccollector-basedfacadeinstallationandpreliminaryassessment.Theresultsincludethesystemdesign,economicanalysisofthesolarphotovoltaiccollector’sapplicationforwaterheating,calculationoftheenergy-savingrate,andfunctionalanalysisofthesolarphotovoltaiccollectorscombinedwithaverticalgreenbalcony.Theoutcomeofthisstudysuggestedthattheprocess-specificrationalizationplancanbeappliedinfutureurbanarchitecturerenovation.